2015
DOI: 10.1371/journal.pone.0131872
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Glioblastoma: Impact of the Combined Use of 5-Aminolevulinic Acid and Intraoperative MRI on Extent of Resection and Survival

Abstract: BackgroundThere is rising evidence that in glioblastoma(GBM) surgery an increase of extent of resection(EoR) leads to an increase of patient’s survival. Based on histopathological assessments tumor depiction of Gd-DTPA enhancement and 5-aminolevulinic-acid-fluorescence(5-ALA) might be synergistic for intraoperative resection control.ObjectiveTo assess impact of additional use of 5-ALA in intraoperative MRI(iMRI) assisted surgery of GBMs on extent of resection(EoR), progression free survival(PFS) and overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 36 publications
1
84
0
Order By: Relevance
“…Age, performance status, extent of surgical resection and MGMT methylation status are well known prognostic factors for GBM patients [4,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][39][40][41][42][43][44]. Nevertheless, the high degree of clinical/molecular heterogeneity found among GBM patients do not generally allow us to correctly classify GBM patients with the use of a single predictor or a few predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, performance status, extent of surgical resection and MGMT methylation status are well known prognostic factors for GBM patients [4,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][39][40][41][42][43][44]. Nevertheless, the high degree of clinical/molecular heterogeneity found among GBM patients do not generally allow us to correctly classify GBM patients with the use of a single predictor or a few predictors.…”
Section: Discussionmentioning
confidence: 99%
“…To classify GBM cases according to this heterogeneity, different prognostic factors have been suggested for GBM, including age, performance status, specific molecular markers [e.g., MGMT methylation (O 6 -methylguanine-DNA methyl-transferase), mutation of IDH1, IDH2(isocitrate dehydrogenase) or TERT (telomerase reverse transcriptase), 1p19q codeletion, overexpression of EGFR (epidermal growth factor receptor)], the size of necrosis and the extent of resection (EOR) [15][16][17][18][19][20][21][22]. The role of EOR in improving survival in patients with GBM has widely been demonstrated, with more extensive resections providing added advantages [8,9,16,18,19,[23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…10,11,25 This has likewise motivated the use of intraoperative 5-aminolevulinic acid fluorescence and electrophysiological mapping and/or intraoperative MRI-assisted surgery in many neurosurgical units in order to reach most radical resections. 8,9,33,35,38 The volumetric measurement of EOR and RTV can be obtained via the manual segmentation of the CET and the postoperative residual, respectively. Kubben et al 23 studied the intrarater and interrater variability of EOR and RTV measurements in 8 patients across 3 different expert raters.…”
mentioning
confidence: 99%
“…A crucial improvement in glioma resection technique was achieved with fluorescence-guided glioma resection [8]. Since this decade, intraoperative MRI has become an additional technical procedure for intraoperative resection control in glioma surgery [2,15,16]. Eyüpoglu et al used high-field (1.5 T) ioMRI and ALA-guided resection and could show that the extent of resection increases from 84 % to 99 % with the additional usage of ioMRI.…”
Section: Discussionmentioning
confidence: 99%
“…In a controlled randomized study with a low-field system, Senft et al [16] detected 96 % gross tumor resection in the patient group who were investigated by ioMRI, versus 68 % gross total resection in the control group. Combining the concept of fluorescence-guided tissue resection and ioMRI, Coburger et al found a higher extent of resection with fluorescence-guided resection and ioMRI (100 %) in comparison to ioMRI alone (82 %) [2]. Gessler et al found that ioMRI und fluorescence guidance were inconsistent in 47 % of patients being resected under surveillance with ioMRI in the first line and fluorescence-guided resection after ALA administration in the second line [17].…”
Section: Introductionmentioning
confidence: 99%